PERSEPSI MAHASISWA IPB INTERNASIONAL BALI TERHADAP PEMBELAJARAN BAHASA INGGRIS SECARA DARING BERBASIS LMS SEBAGAI DAMPAK PANDEMI COVID-19 (NEW NORMAL) - Utik Kuntariati; Putu Sri Darmayanti; Putu Dian Yuliani Paramita3 (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Covid-19, which has been declared a pandemic, has had a massive impact on the viability of people on a global scale. Policies are taken by the governments of each country to immediately overcome the spread of the coronavirus. These policies include wearing masks, washing hands, avoiding crowds, and keeping a distance or better known as social distancing frequently. Social distancing as the impact of covid 19 pandemic has certainly switched from a face-to-face learning system to an online learning system. The change in learning patterns was also implemented by IPB International Bali as a replacement for the face-to-face learning system (offline), which was normally implemented before the pandemic. The study in this article is designed to find out the students’ perceptions of the International Tourism and Business Institute (IPBI) regarding online learning during work from home (WFH). The research method used was a descriptive quantitative method by using Chi-Square with SPSS. The technique of data collection was used through the allocation of questionnaires by using Google Form. Respondents of the research involved 297 students from the majors of Diploma 3 and 4 IPBI. The results of the study indicated that LMS provided benefits in online learning in the midst of the Covid-19 pandemic.